The Knowledge Crisis in Sub-Saharan Africa. To What Extent is the Exchange of Scholarly Knowledge Constrained Across Sub-Saharan Africa to the Detriment of Society and the Economy? Barriers to the Post-2015 Agenda [Sustainable Development Goals] - Huskisson, Mark (2015)
Short Summary Knowledge is seen as a principal currency in the developing global economy, a strategic resource for sustainable development where information has attained the materiality of capital and commodities in the burgeoning knowledge economy. Technological developments have provided an opportunity for disseminating and sharing knowledge equitably to solve critical social issues wherever anyone has access to the Internet. Yet a paradox has evolved whereby digital information has become increasingly commoditised as part of an ‘enclosure of knowledge’ and information poverty is perceived as the single biggest roadblock to sustainable development (Prahalad and Hart, 2002). Institutional theory is used to help identify and conceptualise underlying logics to identify the barriers that exist to the dissemination of the knowledge commons to the widespread benefit and sustainable development of Sub-Saharan Africa. Academic Publishing is conceptualised as an organisational field involved in the creation and dissemination of scholarly knowledge, establishing a virtuous cycle of research and knowledge as a critical aspect in sustainable development. This paper illuminates the constraints that have evolved under the dominant logics that constrain the goals described by the UN’s development agenda for the creation and dissemination of research across developing economies. An interpretivist approach is used to collect data to help identify the personal interpretations to explore how respondents understand research system within their own contexts, thus identifying the institutional logics at play in the organisational field. What is uncovered is a fundamental belief in the market to determine the outcome of two seemingly irreconcilable forces – a recognised need to change the system and the embedded publishing industry where measures have become targets enshrined in assessment and evaluation. Finally I identify a series of unintended consequences from the philanthropic and CSR efforts aimed at resolving the market failure. I conclude that there is a failure of the business models and its constituent parts: the impact factor, copyright and the academic incentive system. That all combine to create a global locational bias that supports the commercial imperative in scholarly publishing to the severe impediment of Sub-Saharan development.